The Upward Spiral Towards Local Integration of IDPs: Agency and Economics in the Democratic Republic of the Congo. (7th January 2021) - Jacobs, Carolien; Lubala Kubiha, Stanislas; Katembera, Rachel Sifa
Abstract: In public discourse, displaced people are often portrayed as burdens to their host communities that add additional pressure to already scarce resources. Recently, scholars and practitioners are paying more attention to the resilience or self-reliance of refugees. Our article takes yet another step by arguing that rather than being dependent or merely self-reliant, displaced people may in fact enrich local economies by introducing products from their communities of origin into the host markets. Based on qualitative research with internally displaced persons in an urban setting in the east of Congo, we show that, through entrepreneurship and innovation, displaced people actually add value to the local economy and carve out their own niche, thanks to their access to resources in their community of origin. This contributes to a more positive attitude among host communities towards displaced and is beneficial to their local integration, but is not a blueprint strategy that can be transferred to other settings.